2018
DOI: 10.1002/jsfa.9443
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic modeling of high‐pressure induced inactivation of polyphenol oxidase in sugarcane juice (Saccharum officinarum)

Abstract: BACKGROUND: Polyphenol oxidase (PPO) is the main enzyme in sugarcane juice associated with rapid browning and degradation of organoleptic properties. High-pressure processing (HPP) (300-600 MPa) of sugarcane juice in combination with moderate temperatures (30-60 ∘ C) for different processing times (10-25 min) has shown promising results in minimizing PPO activity while preserving the juice's freshness. RESULTS:A maximum PPO inactivation of 98% was achieved at 600 MPa/60 ∘ C/25 min, while the corresponding valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 51 publications
(77 reference statements)
0
12
0
Order By: Relevance
“…Sreedevi et al. (2019) obtained Weibull model to best fit the PPO inactivation data during high pressure processing of sugarcane juice. The Weibull distribution model was the most suitable to describe the POD inactivation during ohmic heating of sugarcane juice (Brochier et al., 2016).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sreedevi et al. (2019) obtained Weibull model to best fit the PPO inactivation data during high pressure processing of sugarcane juice. The Weibull distribution model was the most suitable to describe the POD inactivation during ohmic heating of sugarcane juice (Brochier et al., 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The extraction solution was prepared according to Sreedevi et al. (2019). 10 ml of 0.05 M potassium phosphate buffer (pH 7.0) containing 1% (w/v) polyvinylpyrrolidone was added to 10 ml of sugarcane juice sample and mixed in a vortex shaker (Model: 3020, Make: Tarsons Spinix).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Peroxidase (POD) is another such enzyme that promotes darkening of juice where diphenols may function as reducing substrates in the enzymatic reaction. It carries out oxidation only in presence of electron acceptor compounds, like, hydrogen peroxide (H 2 O 2 ) and thus, its contribution in SJ spoilage remains less significant and is not well established (Sreedevi, Jayachandran, & Rao, 2019). However, the effect of POD in causing phenol degradation becomes prominent while coexisting with PPO, owing to generation of H 2 O 2 during PPO catalyzed reactions (Cefola et al, 2012).…”
Section: Spoilage Of Sugarcane Juicementioning
confidence: 99%
“…Fernandez et al (2018) investigated HPP of mixed fruit and vegetable smoothie and reported optimal process pressure of 627.5 MPa for 6.4 minutes with 10% reduction of PPO activity. Sreedevi et al (2019) conducted HPP of sugarcane juice and recorded 98% PPO inactivation at 600MPa for 25 minutes at 60C. PPO inactivation of 57% was achieved when cloudy carrot juice was subjected to HPP at 600 MPa (Stinco et al 2019).…”
Section: Polyphenol Oxidasementioning
confidence: 99%